2021
DOI: 10.1002/app.51281
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of lignin‐based filling antioxidant and its application in styrene‐butadiene rubber

Abstract: A novel filling antioxidant (Lig‐g‐RT) to improve the mechanical properties and antiaging performance of styrene‐butadiene rubber (SBR) composites was prepared by grafting antioxidant intermediate p‐aminodiphenylamine (RT) on the surface of lignin via the linkage of silane coupling agent. Fourier transform infrared (FTIR) and thermogravimetric analysis (TGA) measurements confirmed that RT was successfully grafted on the surface of lignin to produce the functionalized Lig‐g‐RT which shows a better thermal stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The AL also promoted the activation of sulfur to increase the curing rate and cross-link density of rubber, improving the fatigue resistance for NR composites. Zhao et al grafted p -aminodiphenylamine (RT) onto lignin molecules via a bridge of silane coupling agent. The stabilizing effect of the resulted antioxidant Lig- g -RT on the SBR vulcanizates was comparable to that of commercial antioxidant 6PPD, especially the SBR vulcanizate filled with 10 phr of Lig- g -RT showed the optimum antithermo-oxidative properties.…”
Section: Performance Of Rubber/lignin Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The AL also promoted the activation of sulfur to increase the curing rate and cross-link density of rubber, improving the fatigue resistance for NR composites. Zhao et al grafted p -aminodiphenylamine (RT) onto lignin molecules via a bridge of silane coupling agent. The stabilizing effect of the resulted antioxidant Lig- g -RT on the SBR vulcanizates was comparable to that of commercial antioxidant 6PPD, especially the SBR vulcanizate filled with 10 phr of Lig- g -RT showed the optimum antithermo-oxidative properties.…”
Section: Performance Of Rubber/lignin Compositesmentioning
confidence: 99%
“…Possible antioxidization mechanism of the SBR/Lig- g -RT vulcanizate. Reproduced with permission from ref . Copyright 2021 Wiley.…”
Section: Performance Of Rubber/lignin Compositesmentioning
confidence: 99%
“…In this context, amine-functionalized lignin (AL) can be a promising candidate for overcoming the drawbacks of lignin. The aliphatic amine functional groups grafted onto a lignin surface are known as one of the most effective groups for removing ozone and free radicals. , Therefore, AL may impart significantly enhanced aging resistance to rubber compounds compared to that of KL through its radical-scavenging effect. Furthermore, amine-based antioxidants have been reported to open the octatomic rings of S 8 through direct nucleophilic attack, thus accelerating the vulcanization of rubber and generating more active sulfonating agents for rubber curing. This reaction offers the possibility of the antioxidant to participate in the vulcanization reaction with a mechanism similar to that of the accelerator, and it can improve the compatibility of the antioxidant with rubber by maintaining chemical bonds with the rubber chains even after the reaction is completed.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the addition of antioxidants during rubber compounding can delay the aging process of rubber materials and extend their service life. , But most of the traditional rubber antioxidants are small molecular organic compounds, which are easily prone to migration from the polymer matrix during the process and usage. Many studies showed that the migration of antioxidants not only reduces the anti-aging effect of antioxidants but also causes environmental pollution. , In order to overcome the shortcomings of traditional small molecular antioxidants, some effective strategies have been proposed, such as preparing macromolecular antioxidants, reactive antioxidants, and inorganic particle-immobilized antioxidants. Among them, macromolecular antioxidants have attracted wide attention due to their low diffusion rates, excellent extraction resistance, and superior thermal stability. Generally, there are two main methods for preparing macromolecular antioxidants. One way is through the polymerization of functionalized antioxidant monomers.…”
Section: Introductionmentioning
confidence: 99%